Reducing anxiety among teacher candidates: The efficacy of mindfulness-based stress reduction in higher education - Cahyono, Tri; Ariantini, Nisa; Fadilah, Nurul; Muhja, Zainal Abidin; Yulianti, Ika (Edelweiss Applied Science and Technology, 2025)
The high anxiety rate among students, especially prospective teachers, is a significant concern in higher education. Unmanaged anxiety can negatively affect quality of life, academic performance, and professional competence. This study aims to evaluate the effectiveness of Mindfulness-Based Stress Reduction (MBSR) in reducing state and trait anxiety among undergraduate students in education programs. The research employed a quasi-experimental design with a pretest-posttest approach involving 24 participants divided into two groups: an intervention group and a waitlist control group. The intervention group participated in eight sessions of a modified MBSR program tailored for teacher training students, while the waitlist group studied the MBSR material independently. Measurements were taken before and after the intervention using the State-Trait Anxiety Inventory (STAI), and data were analyzed using a 2x2 Repeated Measures ANOVA. Results indicated a significant decrease in both state and trait anxiety in the intervention group following the MBSR program. The average state anxiety score decreased from 55.33 to 49.83, a reduction of 5.5 points, while trait anxiety decreased from 55.33 to 50.25, a reduction of 5.08 points. Conversely, the waitlist group experienced only a slight decrease in state anxiety and a minor increase in trait anxiety. Statistical analysis revealed significant effects of time and group interactions (p < 0.05), with large effect sizes (η² = 0.558 for state anxiety and η² = 0.312 for trait anxiety), indicating that MBSR has a substantial impact on reducing anxiety, particularly in state anxiety.